2009
DOI: 10.1590/s0102-09352009000500004
|View full text |Cite
|
Sign up to set email alerts
|

Presença de animais associada ao risco de transmissão da leishmaniose visceral em humanos em Belo Horizonte, Minas Gerais

Abstract: RESUMOAnalisou-se o risco de se contrair leishmaniose visceral (LV) e a presença de animais em residências de Belo Horizonte/MG, em 2006. O estudo de caso-controle foi feito por meio de visitas domiciliares, aplicação de questionário e registro de imagens da residência. A estimativa de risco foi mensurada por comparação de condições de moradia entre dois grupos: 1-constituído por 82 casos humanos de LV ocorridos em 2004 e 2-164 controles (vizinhos dos casos). Os domicílios pertencentes ao grupo 1 foram os que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 11 publications
(5 reference statements)
1
16
1
9
Order By: Relevance
“…The Jardim União neighborhood is located next to a forest region; however, this variable was not considered as a risk factor for CVL in this study. In addition, the occurrence of the disease in men was statistically associated with cases where the dogs remained inside the home (GAVGANI et al, 2002;BORGES et al, 2009) and the presence of livestock in the property; such relation was not found here, though. In contrast, the presence of agriculture crops around the household was associated to canine leishmaniasis infection with a 1.68 risk of disease occurrence.…”
Section: Discussioncontrasting
confidence: 60%
“…The Jardim União neighborhood is located next to a forest region; however, this variable was not considered as a risk factor for CVL in this study. In addition, the occurrence of the disease in men was statistically associated with cases where the dogs remained inside the home (GAVGANI et al, 2002;BORGES et al, 2009) and the presence of livestock in the property; such relation was not found here, though. In contrast, the presence of agriculture crops around the household was associated to canine leishmaniasis infection with a 1.68 risk of disease occurrence.…”
Section: Discussioncontrasting
confidence: 60%
“…, seguido de los médicos (8,1), mientras los agentes comunitarios de salud tuvieron la menor media (6,7). Las respuestas adecuadas con menos porcentaje de aciertos fueron: medidas preventivas (42,5%), manifestación clínica (25,9%)…”
Section: Objetivounclassified
“…A educação em saúde pode ser uma estratégia capaz de minimizar tais desfechos, pois permite conjugar importantes conceitos do ciclo e sintomatologia das zoonoses aos hábitos e às atitudes da população local. Com essa aproximação, aplicar ações preventivas/curativas realmente eficazes e duradouras torna-se mais tangível, pois elas são desenvolvidas com base nas percepções das comunidades afetadas (8) . Tal processo de educação em saúde deve ser contínuo, permitindo gerar vínculos de compromisso e corresponsabilidade entre a população e os que compõem o sistema de saúde (9) .…”
Section: Introductionunclassified
“…L. longipalpis can adapt to various environments, and its population density is greater inside and around human habitations, which promotes disease transmission (BARATA et al, 2005). Other species including ducks, rodents, passerines, and chickens are considered risk factors for CVL transmission in these regions (BORGES et al, 2009).…”
Section: Introductionmentioning
confidence: 99%